Muscular strength and its relationship to the motor performance of the starting technique among Algerian swimmers in short distances (senior level) - bouadjnak, Kamel; Arabi, Mohammed; bardja, Kamel (sports creativity, 2025)
The objectives of this study are to determine whether muscular power is related to skill in starting at 23 meters, whether biomechanical performance is related to skill in starting at 23 meters, the relationship of performance to muscular power, and whether the performance of Algerian female swimmers differs from that of Algerian male swimmers in terms of the starting technique from a kinetic perspective. Therefore, we used a TOSHIBA laptop (P7), a SONY digital video camera, a video card to transfer the footage from the tape to the computer, the GOM PLAYER software to divide the recording intervals and stop the video at the appropriate time to capture the desired image, an angle measuring device after dividing the video into images, a smooth board, chalk, a level and ruler to measure the vertical jump, and the race adjustment software "REGLAGES DES COURSES" where we entered the race time at 13 meters, giving the ideal starting time at 23 meters. We then digitally recorded the footage and transferred it from the tape to the computer. Using GOM PLAYER, we divided the footage and extracted the images to compare them with the ideal starting distance. The results showed that the level of Algerian swimmers in the starting distance is average compared to international swimmers, based on a comparison of the Algerian swimmers' starting distances. Based on the model start from a kinetic perspective and interviews with coaches, it was found that most coaches are familiar with modern methods used in training for the start technique, but they are confronted with a reality that prevents them from using these methods due to a lack of resources. It was also found that there is an inverse relationship between muscular power and skill in the 23-meter start, as well as with the model timed start, thus confirming the second and third hypotheses. Furthermore, it was found that motor performance is not related to skill in the 23-meter start, nor to muscular power, thus negating the fourth hypothesis. Finally, it was found that there are no differences between Algerian swimmers, both male and female, according to the training programs discussed.